Antihyperglycemic Agents Are Inversely Associated With Intracranial Aneurysm Rupture. Issue 1 (January 2018) - Can, Anil; Castro, Victor M.; Yu, Sheng; Dligach, Dmitriy; Finan, Sean; Gainer, Vivian S.; Shadick, Nancy A.; Savova, Guergana; Murphy, Shawn; Cai, Tianxi; Weiss, Scott T.; Du, Rose
Abstract : Background and Purpose—: Previous studies have suggested a protective effect of diabetes mellitus on aneurysmal subarachnoid hemorrhage risk. However, reports are inconsistent, and objective measures of hyperglycemia in these studies are lacking. Our aim was to investigate the association between aneurysmal subarachnoid hemorrhage and antihyperglycemic agent use and glycated hemoglobin levels. Methods—: The medical records of 4701 patients with 6411 intracranial aneurysms, including 1201 prospective patients, diagnosed at the Massachusetts General Hospital and Brigham and Women's Hospital between 1990 and 2016 were reviewed and analyzed. Patients were separated into ruptured and nonruptured groups. Univariate and multivariate logistic regression analyses were performed to determine the association between aneurysmal subarachnoid hemorrhage and antihyperglycemic agents and glycated hemoglobin levels. Propensity score weighting was used to account for selection bias. Results—: In both unweighted and weighted multivariate analysis, antihyperglycemic agent use was inversely and significantly associated with ruptured aneurysms (unweighted odds ratio, 0.58; 95% confidence interval, 0.39–0.87; weighted odds ratio, 0.57; 95% confidence interval, 0.34–0.96). In contrast, glycated hemoglobin levels were not significantly associated with rupture status. Conclusions—: Antihyperglycemic agent use rather than hyperglycemia is associated with decreased risk of aneurysmal subarachnoid hemorrhage, suggesting a possible protective effect of glucose-lowering agents in the pathogenesis of aneurysm rupture. Abstract : Supplemental Digital Content is available in the text.